Fluorescent probe for detecting early corrosion of metal and preparation method of fluorescent probe

By designing and synthesizing the new Rhodamine fluorescent probe molecule Rhe-M, the problem of the inability to quickly detect early corrosion of carbon steel alloys in the existing technology is solved, and efficient and low-cost detection methods are achieved, and the corrosion protection of the coating is improved. performance.

CN119462677AActive Publication Date: 2025-02-18CHINA SHIPBUILDING INDUSTRY CORPORATION NO725 RESEARCH INSTITUTE
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411598394.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The prior art cannot quickly and sensitively detect early corrosion sites and regions of carbon steel alloys, and the production cost of fluorescent probes is high and the preparation method is complex.

Method used

Design and synthesize a new type of Rhodamine-type organic small molecule fluorescent probe molecule Rhe-M. By adding it to the coating, when the metal is corroded, Fe3+ is chelated with the fluorescent probe, generating a fluorescent signal, thereby Early corrosion was detected.

Benefits of technology

It realizes rapid and sensitive detection of early corrosion sites and regions of carbon steel alloys, reduces production costs, simplifies the preparation method, and significantly improves the corrosion resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462677A_ABST
    Figure CN119462677A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal ion detection, in particular to a fluorescent probe for early corrosion detection of metal and a preparation method of the fluorescent probe, the chemical name of the fluorescent probe is N-[(rhodamine 6G) lactam ethylenediamine]-alpha-furan formaldehyde condensate, and the molecular formula is C35H33N5O3. The fluorescent micromolecule Rh-M sensitive to response to Fe < 3 + > is successfully developed through two-step organic synthesis, the fluorescent micromolecule Rh-M is used as a fluorescent probe molecule capable of recognizing early corrosion sites of carbon steel metal, the fluorescent micromolecule Rh-M acts on the surface layer of the carbon steel, the corrosion sites and the area size of the surface of the carbon steel can be visually observed through irradiation of an ultraviolet lamp, and the fluorescent micromolecule Rh-M can be used as a fluorescent probe molecule for recognizing early corrosion sites of the carbon steel metal. The method is easy and convenient to operate, sensitive in reaction, low in cost and high in specific recognition capacity, and is an efficient method capable of being used for early metal corrosion site detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal ion detection, and in particular to a fluorescent probe for early metal corrosion detection and a preparation method thereof. Background Art

[0002] Corrosion is a phenomenon in which an irreversible chemical reaction occurs between metals and the environment, resulting in the appearance of rust and corrosion pits on the metal surface. Corrosion is extremely harmful, and it not only damages the performance of the metal but also affects the environment. Usually, an anti-corrosion coating is applied to the metal surface to protect the metal from corrosion. However, over time, the coating will age or fail, and the corrosive ions in the environment will gradually enter the metal surface through cracks and holes in the coating, causing severe corrosion on the metal surface. If this phenomenon can be detected by intuitive and simple technical means when the metal corrosion occurs in the early stage, it can play a key role in metal protection. The fluorescent probe is applied to the coating on the metal surface. When corrosion occurs, the Fe generated by the corrosion 2+ It can chelate with the fluorescent probe to specifically generate characteristic fluorescent signals, thereby effectively identifying the site and area of ​​corrosion. Compared with inorganic fluorescent materials and fluorescent materials containing heavy metals, organic small molecule fluorescent materials are not only environmentally friendly and green, but also have the advantages of strong chemical modification, low development cost, and wide fluorescence emission range. Therefore, they are widely used in the detection of various metal ions. Through the construction of the molecular skeleton, the metal cations (Fe 3+ and Fe 2+ ) Organic molecular fluorescent probes that can form chelates or metal complexes to produce strong fluorescence signals when combined with metal ions, thereby intuitively and efficiently detecting early corrosion on the steel surface.

[0003] Publication No.: CN114574070B Damage self-warning anti-corrosion coating doped with zeolite loaded fluorescent probe and preparation method thereof, comprising reacting rhodamine B with anhydrous hydrazine in an anhydrous ethanol environment and under reflux operation conditions to obtain a yellow precipitate and centrifugally wash it, and then drying it to obtain a rhodamine hydrazide fluorescent probe molecule, mixing zeolite powder and the obtained rhodamine hydrazide fluorescent probe molecule in a water-acetonitrile solution, and continuously stirring the reaction to obtain a zeolite loaded fluorescent probe supramolecule, and loading the fluorescent probe on zeolite micro-nano particles to achieve protection of the fluorescent probe and Fe 3+ The corresponding coating damage and local corrosion fluorescent warning. However, the invention is complicated to prepare and the loading efficiency is limited.

[0004] Therefore, there is an urgent need to design a fluorescent probe with low cost, simple preparation method, and the ability to quickly and sensitively detect early corrosion sites and areas of carbon steel alloys. Summary of the invention

[0005] In view of this, the present invention aims to propose a fluorescent probe for early metal corrosion detection and a preparation method thereof, so as to solve the problems in the prior art that the early corrosion sites and regions of carbon steel alloys cannot be detected quickly and sensitively and the problems that the production cost of fluorescent probes is high and the preparation method is complicated.

[0006] Carbon steel alloys are susceptible to moisture corrosion in the external environment, and it is difficult to achieve efficient metal ion specific identification and early corrosion monitoring in actual applications. We designed and synthesized a new type of rhodamine-based organic small molecule fluorescent probe molecule and added this type of material to the coating as a fluorescence indicator. No fluorescence is generated when there is no corrosion; when the metal corrodes, the iron ions Fe 3+ It chelates with the fluorescent probe to generate fluorescence, thereby quickly and sensitively detecting the early corrosion sites and areas of carbon steel alloys.

[0007] At the same time, the probe Rhe-M of the present application can be used as a chemical adsorption layer coated on the surface of carbon steel, which can delay the occurrence of corrosion to a certain extent and enhance the adsorption capacity of the coating.

[0008] The technical solution of the present invention is achieved in this way:

[0009] The first object of the present invention is to disclose a fluorescent probe for early metal corrosion detection. The chemical name of the fluorescent probe is: N-[(rhodamine-6G) lactam ethylenediamine]-α-furan carboxaldehyde condensate, and the molecular formula is: C 35 H 33 N5O3, its structural formula is shown in formula (1):

[0010]

[0011] Furthermore, the method for using the fluorescent probe is as follows: Rhe-M is added to L-6030 acrylic resin, and stirred using a magnetic stirrer or a high-speed stirrer for 30 minutes to 1 hour to form a uniform coating, and then the coating is evenly applied to the surface of carbon steel. The curing time is one week, and the corrosion sites and area sizes on the surface of the carbon steel are observed by irradiation with ultraviolet light.

[0012] Furthermore, Rhe-M has a significant effect on Fe 3+ The detection limit (LOD) was 2.29×10 -6 M.

[0013] Another object of the present invention is to disclose a method for preparing a fluorescent probe for early metal corrosion detection, which is used to prepare the fluorescent probe for early metal corrosion detection described in claim 1, comprising the following specific steps:

[0014] S1: under condensation reflux conditions, rhodamine 6G and ethylenediamine are added to a solvent for mixed reaction, and cooled to room temperature to obtain an intermediate product Rhe;

[0015] S2: purifying the solid product Rhe obtained in step S1;

[0016] S3: Under condensation reflux conditions, the intermediate product Rhe and α-furfurylaldehyde are added to a solvent and mixed, and after the reaction is complete, a brown powder Rhe-M is obtained.

[0017] Furthermore, in step S1, the ratio of the amount of rhodamine 6G to ethylenediamine is 1:(0.8-1.4), and the condensation reflux time is 4 hours.

[0018] Further, in step S2, the product Rhe is washed with a solvent, recrystallized with acetonitrile, and then dried in vacuo to obtain a white powder product.

[0019] Further, in step S3, the ratio of the amount of the intermediate product Rhe to α-furfural is 1:(1.1-1.5), and the mixture is condensed and refluxed for 8 hours.

[0020] Furthermore, in step S3, the ratio of the amount of the intermediate product Rhe to the amount of α-furan carboxaldehyde is 1:(1.1-1.5).

[0021] Furthermore, in step S3, TCL is used to detect the reaction progress.

[0022] Furthermore, the solvent is one of methanol, ethanol and dioxane.

[0023] Furthermore, the reaction temperature is 65-120°C, and the reaction time is 2-12h.

[0024] Compared with the prior art, the method for preparing a fluorescent probe for early metal corrosion detection of the present invention has the following advantages:

[0025] 1. The present invention successfully developed Fe through two-step organic synthesis 3+ The responsive fluorescent small molecule Rhe-M is used as a fluorescent probe molecule that can identify the early corrosion sites of carbon steel metal. When it is applied to the surface layer of carbon steel, the corrosion sites and area sizes on the carbon steel surface can be intuitively observed through irradiation with ultraviolet light. This method is simple to operate, sensitive, low-cost, and has strong specific recognition ability. It is an efficient method that can be used for the detection of early metal corrosion sites.

[0026] 2. The present invention uses the unique "off-on" mechanism of the rhodamine lactam ring, Rhe-M to Fe 3+ The detection limit (LOD) was 2.29×10 -6M, detects the occurrence of early metal corrosion and significantly improves the ability to detect early metal corrosion.

[0027] 3. The present invention introduces N and O heteroatoms, which is beneficial to the physical and chemical adsorption of probe molecules on the carbon steel surface. The impedance value of the corrosion-sensitive coating is still as high as 3.47×10 7 (Ω / cm 2 ), the addition of Rhe-M significantly improves the anti-corrosion performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0029] Figure 1 It is a synthesis diagram of the intermediate Rhe of the present invention;

[0030] Figure 2 It is a synthetic diagram of the Rhe-M fluorescent small molecule of the present invention;

[0031] Figure 3 is the fluorescent molecule Rhe-M of the present invention 1 H NMR spectrum;

[0032] Figure 4 is the FT-IR spectrum of the fluorescent molecule Rhe-M of the present invention;

[0033] Figure 5 is the FT-IR spectrum of the fluorescent molecule Rhe-M of the present invention;

[0034] Figure 6 is the HRMS spectrum of the fluorescent molecule Rhe-M of the present invention;

[0035] Figure 7 The fluorescence spectra of Rhe-M (100 μmol / L) and different metal ions (100 μmol / L) of the present invention are shown in Figure 1. ex =347nm);

[0036] Figure 8 The present invention is a method for treating Rhe-M (100 μmol / L) and 30 μL of Fe 3+ (100 μmol / L) in the presence of 30 μL of other metal ions (100 μmol / L) added respectively;

[0037] Fig. 9 The present invention (a) has different concentrations (0-250 mol / L) of Fe 3+Comparison of fluorescence intensity after adding 100 μmol / L fluorescent molecule Rhe-M; (b) Under irradiation with an excitation wavelength of 347 nm, the fluorescence intensity is comparable to that of Fe 3+ Linear relationship between Rhe-M and different concentrations (0-250 μmol / L) of Fe under (c) natural light and (d) UV light 3+ Intuitive diagram;

[0038] Fig.10 The present invention (a) is a fluorescent molecule Rhe-M and (0-250 μmol / L) Fe 3+ (a) UV absorption spectrum of the OLED, (b) linear regression curve of the UV absorption spectrum corresponding to the excitation wavelength of 520 nm;

[0039] Fig.11 The adhesion of Rhe-M added in an amount of 1wt% and 2wt% to L-6030 coating of the present invention;

[0040] Fig.12 (a) The contact angle of the L-6030 coating of the present invention; (b) The contact angle of the L-6030 coating with the addition of the probe Rhe-M;

[0041] Fig.13 The Nyquist curves of (a) L-6030 and (c) L-6030 coating doped with Rhe-M (2 wt%) in 3.5 wt% NaCl solution of the present invention over time; the Bode plots of (b) L-6030 and (d) L-6030 coating doped with Rhe-M (2 wt%) over time;

[0042] Fig.14 The Tafel polarization curves of (a) the L-6030 coating of the present invention immersed in a 3.5wt% NaCl solution; (b) the Tafel polarization curves of the L-6030 coating doped with Rhe-M immersed in a 3.5wt% NaCl solution;

[0043] Fig.15 The present invention (a) is a SEM image of a scratched L-6030 coating after immersion in a 3.5% NaCl solution for 4 days; (b) is a SEM image of a scratched L-6030 coating doped with Rhe-M after immersion in a 3.5% NaCl solution for 4 days;

[0044] Fig.16 The scratch corrosion images of the L-6030 coating doped with Rhe-M after being immersed in 3.5wt% NaCl for (a) 0h, (b) 1h, (c) 2h, and (d) 4h under optical microscope and fluorescence microscope under the same exposure parameters of the present invention;

[0045] Fig.17It is the frontier orbital and electrostatic potential distribution of the fluorescent molecule Rhe-M of the present invention. DETAILED DESCRIPTION

[0046] In order to make the technical means, objectives and effects of the present invention easy to understand, the embodiments of the present invention are described in detail below with reference to specific drawings.

[0047] It should be noted that all the terms used in the present invention to indicate directionality and position, such as "upper", "lower", "left", "right", "front", "back", "vertical", "horizontal", "inside", "outside", "top", "lower", "lateral", "longitudinal", "center", etc., are only used to explain the relative positional relationship and connection status between the components in a certain state, and are only for the convenience of describing the present invention, rather than requiring the present invention to be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the descriptions of "first", "second", etc. in the present invention are only used for descriptive purposes, and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features.

[0048] In the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0049] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0050] The first object of the present invention is to disclose a fluorescent probe for early metal corrosion detection. The chemical name of the fluorescent probe is: N-[(rhodamine-6G) lactam ethylenediamine]-α-furan formaldehyde condensate, and the molecular formula is: C 35 H 33 N5O3, its structural formula is shown in formula (1):

[0051]

[0052] In this setting, Rhe-M has a high sensitivity to Fe, can detect low concentrations of Fe, effectively distinguish other metal ions, reduce interference, and has high selectivity. After Rhe-M binds to Fe, the fluorescence response is rapid, which is suitable for real-time detection. At the same time, Rhe-M has good biocompatibility and can be used in biological systems.

[0053] The second object of the present invention is to disclose a method for preparing a fluorescent probe for early metal corrosion detection, comprising the following specific steps:

[0054] S1: Rhodamine 6G and ethylenediamine were mixed and reacted under methanol and condensation reflux conditions, and then cooled to room temperature to obtain an intermediate product Rhe;

[0055] S2: purifying the solid product Rhe obtained in step S1;

[0056] S3: Under the conditions of methanol and condensation reflux, the intermediate product Rhe and α-furfural are mixed, and after the reaction is complete, a brown powder Rhe-M is obtained.

[0057] Rhodamine 6G reacts with ethylenediamine to form N-(rhodamine-6G) lactam ethylenediamine (Rhe). The introduction of ethylenediamine improves the water solubility of Rhe, making it more suitable for use in aqueous systems. Unreacted raw materials and by-products are then removed to improve the purity of the product, ensuring its purity and fluorescence properties. Finally, Rhe reacts with α-furfurylaldehyde to form Fe 3+ The probe Rhe-M has specific fluorescence properties and metal ion detection capabilities.

[0058] The preparation method has mild reaction conditions, moderate yield, simple overall operation and good purity.

[0059] Preferably, the solvent is methanol, which may also be replaced by one of ethanol and dioxane.

[0060] This setting provides flexibility in the choice of solvent, and the most suitable solvent can be selected according to specific experimental conditions and requirements to improve the efficiency and yield of the reaction.

[0061] Specifically, the reaction temperature during the entire reaction process is 65-120° C., and the reaction time is 2-12 hours.

[0062] The temperature range of 65-120°C can provide sufficient energy to promote the reaction while avoiding side reactions or decomposition of reactants caused by excessively high temperatures. The reaction time of 2-12 hours provides sufficient time for the reactants to fully contact and react, ensuring the complete reaction and improving the yield and purity of the product.

[0063] By rationally selecting and controlling these parameters, this setting can ensure the efficient progress of the reaction, improve the yield and purity of the product, and meet the needs of early metal corrosion detection.

[0064] Specifically, in step S1, the ratio of the amount of rhodamine 6G to ethylenediamine is 1:(0.8-1.4).

[0065] In actual operation, in order to ensure that the reaction is completely carried out, one reactant is usually added in a slightly excessive amount. For example, if ethylenediamine is slightly excessive (such as 1.1 times), it can ensure that all rhodamine 6G can react with ethylenediamine, thereby improving the completion of the reaction, reducing the occurrence of side reactions, and thus increasing the yield of the target product.

[0066] Preferably, the ratio of the amount of rhodamine 6G to ethylenediamine is 1:1.2. For example, the mass of rhodamine 6G is 3 g, and the mass of ethylenediamine is 0.45 g.

[0067] Specifically, in step S1, the condensation reflux time is 4 hours.

[0068] The 4-hour condensation reflux time provides enough time for the reactants to fully contact and react, thereby ensuring the complete progress of the reaction. The condensation reflux device can maintain the reaction system at a constant temperature, which helps to maintain the stability of the reaction conditions and avoid incomplete reactions or side reactions caused by temperature fluctuations. Longer condensation reflux time can increase the depth of the reaction, convert more reactants into products, thereby improving the yield, effectively recovering the volatile solvent, reducing the loss of solvent, and reducing costs.

[0069] Specifically, in step S2, a solvent is used for washing, acetonitrile is used for recrystallization, and then vacuum drying is performed to obtain a white powder product Rhe.

[0070] Rhe can be further purified by washing with methanol and recrystallizing with acetonitrile to remove unreacted raw materials and by-products and improve the purity of the product to ensure its purity and fluorescence properties.

[0071] This setup ensures the purity of Rhe through multiple washing and recrystallization, improves the efficiency of subsequent reactions and the performance of the product, and the overall process is relatively simple.

[0072] Specifically, in step S3, the ratio of the amount of the intermediate product Rhe to the amount of α-furan carboxaldehyde is 1:(1.1-1.5).

[0073] By adding α-furfural in a slightly excessive amount, it can be ensured that all Rhe can react with α-furfural. Excess α-furfural can reduce side reactions and can also be removed through simple separation and purification steps, simplifying the post-processing process.

[0074] This setup helps to improve the completeness of the reaction, ensure the selectivity and purity of the target product, and can reduce the total reaction time and post-processing steps, thereby reducing the overall cost and achieving high efficiency, high yield and high purity of the target product.

[0075] Specifically, in step S3, condensation and reflux are performed for 8 hours.

[0076] The 8-hour condensation reflux time provides enough time for the reactants to fully contact and react, thereby ensuring the complete progress of the reaction. The condensation reflux device can maintain the reaction system at a constant temperature, which helps to maintain the stability of the reaction conditions and avoid incomplete reactions or side reactions caused by temperature fluctuations. Longer condensation reflux time can increase the depth of the reaction, convert more reactants into products, thereby improving the yield, effectively recovering the volatile solvent, reducing the loss of solvent, and reducing costs.

[0077] Specifically, in step S3, TCL is used to detect the reaction progress.

[0078] TLC is a fast, simple and sensitive analytical technique widely used in organic synthesis to monitor the progress of reactions, determine whether reactions are complete and assess the purity of products. TLC can complete a test within a few minutes, making it ideal for frequently monitoring the progress of reactions during the course of a reaction.

[0079] By taking samples regularly and performing TLC analysis, we can understand the consumption of reactants and the generation of products in real time, and adjust the reaction conditions in time to avoid overreaction, reduce the generation of by-products, improve the purity of the target product, and help determine whether the reaction has been completed.

[0080] The setup is simple to operate and does not require complex instruments. The TLC results are presented in the form of spots, which are intuitive and easy to understand, observe and record.

[0081] Specifically, the method of using the fluorescent probe is as follows: add Rhe-M to L-6030 acrylic resin, use a magnetic stirrer or a high-speed stirrer to stir for 30 minutes to 1 hour to form a uniform coating, and then apply the coating evenly to the carbon steel surface. The curing time is one week. Through the irradiation of ultraviolet light, the corrosion sites and area sizes on the carbon steel surface are observed.

[0082] The addition of Rhe-M significantly reduces the self-corrosion current density of the coating from 1×10 -8 A / cm 2 Reduced to 1×10 - 10 A / cm 2, which enhances the physical barrier effect of the coating, reduces the diffusion path of the corrosive medium, improves the anti-penetration ability of the coating, improves the adhesion between the coating and the substrate, and makes the coating more firm and not easy to fall off.

[0083] This setting can significantly improve the corrosion resistance of the coating, reduce the generation of corrosion products, reduce pollution to the environment, and is simple to operate and easy to implement.

[0084] Preferably, 2 wt% of Rhe-M is added to L-6030 acrylic resin.

[0085] Preferably, the curing time is 4 days.

[0086] Specifically, Rhe-M to Fe 3+ The detection limit (LOD) was 2.29×10 -6 M.

[0087] Rhe-M to Fe 3+ The detection limit was 2.29×10 -6 M, indicating that it has high sensitivity and can detect very low concentrations of Fe 3+ In many applications, such as water quality monitoring, industrial production process control, etc., trace Fe 3+ Ions are critical to preventing potential problems, and Rhe-M has a significant effect on Fe 3+ The specific response of Rhe-M and Fe 3+ The binding reaction of ions is rapid and the detection can be completed in a short time. It is suitable for rapid on-site detection, easy to operate and does not require complicated pre-treatment steps.

[0088] This setup enables Rhe-M to accurately and rapidly detect Fe 3+ ions to ensure the reliability and accuracy of the test results.

[0089] Embodiment 1:

[0090] Preparation of Rhe-M

[0091] Rhe synthesis reaction formula is as follows Figure 1 , Rhodamine 6G (3.0 g, 6.26 mmol) and ethylenediamine (0.45 g, 7.51 mmol) were weighed and placed in a 100 mL round-bottom flask, 25 mL of methanol was added, condensed and refluxed for 4 h, cooled to room temperature, filtered, washed with methanol, recrystallized with acetonitrile, and dried in vacuo to obtain 2.14 g of white powder product Rhe (yield 74.8%).

[0092] The Rhe-M synthesis reaction is as follows Figure 2, weigh the intermediate product Rhe (200.0 mg, 0.438 mmol) and α-furan carboxaldehyde (48.0 mg, 0.525 mmol) into a 150 mL round-bottom flask, add 20 mL of methanol, condense and reflux for 8 h, monitor the reaction progress by TCL, and after the reaction is complete, wash with methanol to obtain 101 mg of brown powder Rhe-M (yield 43.2%).

[0093] Example 2

[0094] Rhodamine Fe 3+ Basic structural characterization of fluorescent probe small molecules

[0095] The prepared Rhe-M small molecule was dried in a vacuum oven for 24 hours. The solid sample was subjected to hydrogen nuclear magnetic resonance spectroscopy. 1 H-NMR( Figure 3 ), Fourier transform infrared spectroscopy ( Figure 4 )、( Figure 5 ) and high-resolution mass spectrometry ( Figure 6 ) test to verify the correctness of the product structure.

[0096] Example 3

[0097] Rhe-M small molecule optical sensing performance test

[0098] Rhe-M ligand stock solution and Fe 3+ Preparation of stock solution: Prepare a 100 μmol / L Rhe-M stock solution in dichloromethane; prepare a 1 mol / L stock solution of FeCl3·6H2O in water, and dilute different concentrations (50 μmol / L, 100 μmol / L, 150 μmol / L, 200 μmol / L, 250 μmol / L) of Fe 3+ The fluorescence test was performed on it, with the excitation wavelength set to 347nm and the wavelength range of 200-800nm, to measure the fluorescence emission of Rhe-M in ethanol solution.

[0099] Example 4

[0100] Selectivity test of ligand Rhe-M for different metal ions

[0101] Figure 7 For the fluorescence spectra of Rhe-M and metal ions, add 30 μL of Fe 3+ When added to Rhe-M (100 μmol / L) solution, the fluorescence intensity was significantly enhanced, with the amplitude (1-I0 / I) reaching 95.14%. Under the same conditions, when the same amount of Ag was added to the Rhe-M solution, + , Ba 2+ , Ca 2+ 、Cd2+ 、Co 2+ Cr 3+ The fluorescence of the ligand Rhe-M does not change much when the metal ion stock solution is used. 3+ It has a highly selective recognition ability, which may be attributed to the fact that Rhe-M contains abundant N, O and other coordination sites, which can bind to Fe 3+ Chelation occurs, causing the lactam to break and open its ring, and the fluorescence of the system is enhanced.

[0102] Example 5

[0103] Rhe-M-Fe 3+ Anti-interference test

[0104] To the EtOH solution of Rhe-M (100 μmol / L), 30 μL of Fe 3+ Stock solution, add equal amounts of other metal ions (Ag + , Ba 2+ , Ca 2+ 、Cd 2+ 、Zn 2+ Cr 3+ The fluorescence intensity changes as Figure 8 The results showed that other metal ions would not affect Rhe-M-Fe 3+ The fluorescence intensity of Fe 2+ Although the impact is large, Fe 2+ Extremely unstable, easily oxidized to Fe 3+ , indicating that Rhe-M-Fe 3+ The selective recognition has excellent anti-interference performance.

[0105] Example 6

[0106] Different concentrations of Fe 3+ Fluorescence performance test of ligand Rhe-M

[0107] Fluorescence titration of Rhe-M and Fe 3+ The relationship between concentration. Fig. 9 -a indicates that with Fe 3+ With the increase of concentration, the fluorescence intensity of Rhe-M gradually increased and reached the highest at 250 μmol / L. The solution turned red under natural light and yellow fluorescence under ultraviolet light. 3+ The concentration of is plotted as the horizontal axis and the fluorescence intensity I of the complex as the vertical axis, and a calibration curve with a linear equation of y = 2759.17x + 189.12 and R2 = 0.998 is obtained ( Fig. 9 -b). The detection limit (LOD) was calculated to be 2.292×10 -6M, indicating that Rhe-M has an effect on Fe 3+ Has higher sensitivity.

[0108] Example 7

[0109] UV spectrum test

[0110] Fig.10 For Rhe-M in different Fe 3+ The UV absorption spectrum at different concentrations (0-250 μmol / L) and the linear regression curve of the UV absorption intensity at an excitation wavelength of 520 nm show that the ligand Rhe-M has a strong UV absorption at 430 nm, which belongs to the UV absorption of the -C=N- double bond on the Schiff base in Rhe-M. 3+ As the concentration continued to increase, a strong UV absorption peak was generated at a wavelength of 520nm, which was attributed to the UV characteristic absorption peak after the opening of rhodamine spirolactam. Another absorption peak appeared at 353nm, indicating that Fe 3+ After interacting with the ligand, new substances are generated. The linear equation of the regression line is y = 0.17446x + 0.0051, and the correlation coefficient R2 = 0.96574. The UV absorption spectrum test shows that Rhe-M can be used as a detection of Fe 3+ The probe effect is excellent.

[0111] Example 8

[0112] Adhesion performance test

[0113] Apply L-6030 acrylic resin evenly on the surface of Q235 carbon steel and wait for the coating to cure for one week. The adhesion data of the fluorescent probe Rhe-M on the L-6030 coating are as follows Fig.11 As shown, it can be seen that the adhesion of L-6030 coating is poor, with an average of 3.192N / cm 2 After adding Rhe-M, the L-6030 coating has a good change. When the addition amount is 2wt%, the average adhesion is 5.196N / cm 2 , indicating that the doping of Rhe-M improves the adhesion between the coating and the carbon steel substrate.

[0114] Example 9

[0115] Contact angle performance test

[0116] The contact angle of the prepared L-6030 composite coating was tested. In this experiment, 5 points were randomly selected as parallel experiments to eliminate experimental errors. Fig.12As shown in the figure, the contact angle θ between the L-6030 coating and water is 69.6°, indicating that the L-6030 coating is hydrophilic and easily damaged by corrosive media in water. The contact angle θ of the L-6030 coating with Rhe-M added is 81.2°. The hydrophobicity of the layer is enhanced and the corrosion resistance is significantly improved.

[0117] Example 10

[0118] Coating electrochemical testing

[0119] Fig.13 The Nyquist curves and Bode diagrams of L-6030 coating and Rhe-M-added coating. Nyquist curves of (a) L-6030 and (c) L-6030 coating doped with Rhe-M (2wt%) over time in 3.5% NaCl solution; Bode diagrams of (b) L-6030 and (d) L-6030 coating doped with Rhe-M (2wt%) over time. As the immersion time increases, the impedance arc radius in the Nyquist diagram decreases, indicating that the overall anti-corrosion performance of the coating decreases. After immersion for 4 days, the impedance modulus value │Z│ of the coating with Rhe-M increases from 5.93×10 8 (Ω·cm 2 ) decreased to 3.47×10 7 (Ω·cm 2 ), the impedance modulus of the blank L-6030 coating │Z│ is 7.87×10 5 (Ω·cm 2 ) decreased to 4.14×10 4 (Ω·cm 2 ), the impedance modulus of the Rhe-M coating is always 3 orders of magnitude higher than that of the blank coating, and Rhe-M enhances the anti-corrosion performance of the coating.

[0120] Fig.14 The Tafel polarization curves of L-6030 coating and coating with Rhe-M added are shown in Figure 2. The self-corrosion potential of L-6030 coating is -0.60V, and the corrosion potential of L-6030 coating with Rhe-M added is positively shifted to about -0.30V, which significantly reduces the tendency of carbon steel plate to corrode toward the anode. The self-corrosion current density refers to the corrosion current intensity per unit metal area. The lower the corrosion current value, the higher the degree of corrosion resistance of the coating. The self-corrosion current density of L-6030 coating is 1×10 -8 A / cm 2 As the immersion time increases, the self-corrosion current density gradually decreases to 1×10 -6 A / cm 2 , while the corrosion current density of L-6030 coating with Rhe-M added reaches 1×10 -10 A / cm2 , indicating that the L-6030 coating doped with Rhe-M has better corrosion resistance, which is consistent with the results obtained from the above-mentioned AC impedance test.

[0121] Embodiment 11

[0122] Microscopic morphology of coating scratches (SEM electron microscope analysis)

[0123] Fig.15 The SEM images of the scratches of the L-6030 coating and the coating doped with Rhe-M (2wt%) are shown below. Due to the intrusion of corrosion ions, the microscopic surface of the coating is mostly a fragmented resin layer, indicating that the coating begins to fall off and fail after corrosion. Compared with the coating doped with Rhe-M, we can clearly see that the coating is more complete in microscopic appearance and has fewer tiny pores, indicating that doping with Rhe-M protects the L-6030 coating to a certain extent.

[0124] Example 12

[0125] Response performance of Rhe-M to corrosion of L-6030 coating

[0126] Fig.16 The images of the L-6030 coating doped with Rhe-M under an optical microscope and a fluorescence microscope. After the metal substrate is scratched, the metal substrate exposed under the scratch can be clearly seen under an optical microscope. When it is not immersed in NaCl solution, no obvious changes are seen under the fluorescence microscope. When the carbon steel sample is immersed in NaCl solution for 1 hour ( Fig.16 -b), corrosion products were observed in the scratches of the coating under an optical microscope, and orange-yellow fluorescence could be vaguely seen at the scratches under a fluorescence microscope. Fig.16 -c), the scratches showed a distinct light pink color under an optical microscope, and a clear orange fluorescence appeared under a fluorescence microscope, which indicated that the metal corroded to generate Fe 3+ Reaction with fluorescent probe Rhe-M to emit fluorescence. Soak for 4h ( Fig.16 -d), the fluorescence intensity becomes slightly weaker, and there is a tendency for fluorescence disappearance at the scratch.

[0127] Example 13

[0128] Frontier orbitals and electrostatic potential distribution of fluorescent molecule Rhe-M

[0129] The relationship between Rhe-M and Fe was investigated by analyzing and calculating the HOMO and LUMO orbitals and electrostatic potential (ESP). 3+ The interaction between ions. Fig.17As shown in the figure, the HOMO of Rhe-M is discretely distributed in the benzene ring on the left side of the xanthene, while the LUMO is mainly distributed in the -N=CH- group and the furan ring unit. After the addition of Fe, the distribution of HOMO and LUMO has changed significantly. The LUMO is more distributed in the spirolactam ring opening and the furan ring, and the HOMO is more concentrated in the xanthene aromatic ring, basically occupying the energy gap of the entire aromatic ring Rhe-M-Fe (ΔE=E LUMO -E HOMO ) showed that the Rhe-M-Fe complex was more stable than Rhe-M, that is, ΔE Rhe-M-Fe =2.22eV<ΔE Rhe-M =4.49eV).

[0130] Embodiment 14

[0131] By changing the synthetic feed ratio (Rhe: α-furfural), different solvents (methanol, ethanol and dioxane), reaction temperature (65 degrees Celsius-120 degrees Celsius) and reaction time (2h to 12h) and other conditions, the best reaction conditions for the preparation of Rhe-M were finally obtained after continuous attempts and multiple experimental optimizations. The optimized preparation conditions are as follows:

[0132] S1 and S2: Preparation and purification of Rhe

[0133]

[0134] S3: Development of Rhe-M

[0135]

[0136] The developed Rhe-M was tested for fluorescence and prepared with different concentrations (0-250 μmol / L) of Fe 3+ Add 100 μmol / L Rhe-M ethanol solution to test the fluorescence intensity. The specific implementation method and results are shown in the following table:

[0137] Example 3: Fluorescence intensity test

[0138]

[0139]

[0140] The present invention successfully developed a fluorescent small molecule Rhe-M that is sensitive to Fe3+ through a two-step organic chemical reaction. Through the study of fluorescence sensing performance, the detection limit (LOD) was calculated to be 2.292×10 -6 M, indicating that Rhe-M has an effect on Fe 3+It has high sensitivity and good anti-interference to other metal ions. When added to L-6030 acrylic resin at 2wt%, the early corrosion of carbon steel was detected. At the same time, the anti-corrosion performance of L-6030 coating was measured, which showed that the probe Rhe-M can be used as a chemical adsorption layer on the surface of carbon steel, delaying the occurrence of corrosion to a certain extent. Therefore, Rhe-M's excellent early corrosion detection ability and anti-corrosion properties make it have broad application prospects and practical value in the fields of metal corrosion protection, coating industry, and ship engineering.

[0141] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A fluorescent probe for early metal corrosion detection, characterized in that: The chemical name of the fluorescent probe is: N-[(rhodamine-6G) lactam ethylenediamine]-α-furfurylaldehyde condensate, and the molecular formula is: C 35 H 33 N5O3, its structural formula is shown in formula (1):

2. The fluorescent probe for early metal corrosion detection according to claim 1, characterized in that: The method for using the fluorescent probe is as follows: Rhe-M is added to L-6030 acrylic resin, and stirred with a magnetic stirrer or a high-speed stirrer for 30 minutes to 1 hour to form a uniform coating, and then the coating is evenly applied to the surface of carbon steel. The curing time is one week, and the corrosion sites and area sizes on the surface of the carbon steel are observed by irradiation with ultraviolet light.

3. The fluorescent probe for early metal corrosion detection according to claim 1, characterized in that: Rhe-M to Fe 3+ The detection limit (LOD) was 2.29×10 -6 M.

4. A method for preparing a fluorescent probe for early metal corrosion detection, characterized in that: The method for preparing the fluorescent probe for early metal corrosion detection as described in claim 1 comprises the following specific steps: S1: under condensation reflux conditions, rhodamine 6G and ethylenediamine are added to a solvent for mixed reaction, and cooled to room temperature to obtain an intermediate product Rhe; S2: purifying the solid product Rhe obtained in step S1; S3: Under condensation reflux conditions, the intermediate product Rhe and α-furfurylaldehyde are added to a solvent and mixed, and after the reaction is complete, a brown powder Rhe-M is obtained.

5. The method for preparing a fluorescent probe for early metal corrosion detection according to claim 4, characterized in that: In step S1, the ratio of the amount of rhodamine 6G to ethylenediamine is 1:(0.8-1.4), and the condensation reflux time is 4 hours.

6. The method for preparing a fluorescent probe for early metal corrosion detection according to claim 4, characterized in that: In step S2, the product Rhe is obtained by washing with a solvent, recrystallizing with acetonitrile, and then vacuum drying.

7. The method for preparing a fluorescent probe for early metal corrosion detection according to claim 4, characterized in that: In step S3, the ratio of the amount of the intermediate product Rhe to α-furfural is 1:(1.1-1.5), and the mixture is condensed and refluxed for 8 hours.

8. The method for preparing a fluorescent probe for early metal corrosion detection according to claim 4, characterized in that: In step S3, the progress of the reaction is monitored using TCL.

9. The method for preparing a fluorescent probe for early metal corrosion detection according to claim 4, characterized in that: The solvent is one of methanol, ethanol and dioxane.

10. The method for preparing a fluorescent probe for early metal corrosion detection according to claim 4, characterized in that: The reaction temperature is 65-120°C and the reaction time is 2-12h.

Citation Information

Patent Citations

  • Rhodamine B luminescent material containing furfural heterocyclic ring, preparation method and application to fluorescent sensing

    CN107417693A

  • Preparation method and application of rhodamine B luminous material based on furoyl chloride

    CN108358938A

  • Fluorescence probe for detecting iron ions, preparation and application

    CN108949157A

  • Rhodamine fluorescent probe containing furan structure as well as synthesis method and application of rhodamine fluorescent probe

    CN117736217A